A literature review of the patent application publications on cabotegravir – an HIV integrase strand transfer inhibitor. (3rd March 2020) - Kovač, Lidija; Časar, Zdenko
ABSTRACT: Introduction : Studies presented in the patent applications demonstrate that a new integrase strand transfer inhibitor cabotegravir might be used as long-acting antiretroviral formulation or delivery system that reduces dosing frequency and may therefore increase adherence and thus pre-exposure prophylaxis (PrEP) and treatment efficacy against HIV. As announced in 2019, the developer ViiV Healthcare seeks US and EU approval of long-acting, injectable HIV treatment. Area covered : This review covers all the patent applications published until October 2019 with cabotegravir in the examples or claim section of the patent application document. The patent applications cover drug substance synthesis, solid-state forms, therapeutic applications, in vitro and in vivo efficacy as well as the potential formulations of cabotegravir alone or in combination with other anti-HIV agents. Expert opinion : The results from multiple clinical studies suggest that cabotegravir can be used as PrEP agent and treatment agent against HIV. Multiple studies use cabotegravir in combination with other anti-HIV agents such as rilpivirine. Cabotegravir in combination with rilpivirine is an interesting therapeutic, due to the possibility of formulating long-acting formulation with dosing interval of every 4 weeks or less, thus reducing daily pill burden and improving patient's compliance.